Peningkatan Pengetahuan Diabetes Militus Pada Wanita Usia Subur 15-49 Tahun Di Wilayah Kerja Puskesmas Pakutandang Kabupaten Bandung Tahun 2025: Penelitian - Ahmad Zaelani; Wahyu Nursidik; Nurul Camelia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Diabetes is a non-communicable disease that has become a global health issue, including in the Republic of Indonesia. According to Riskesdas data, 70% of people with diabetes mellitus are unaware that they have the disease. One of the causes of diabetes mellitus is an instant lifestyle. Diabetes mellitus has a significant impact on health and can cause complications in the long term. Women have a higher risk of developing type 2 diabetes mellitus than men. In women of childbearing age, diabetes mellitus can affect reproductive health and pregnancy quality, which in turn can affect the next generation. The objective of this community service programme is to increase knowledge about preventing diabetes mellitus in women of childbearing age (15-49 years) in the Pakutandang Community Health Centre working area in Bandung Regency. Method: This community service activity was carried out through lectures, in coordination with the community health centre, then women of childbearing age were gathered in a multipurpose building located near the village of Pakutandang. Results: The results showed that education can increase knowledge about diabetes mellitus among women of childbearing age (15-49 years) in the working area of the Pakutandang Community Health Centre in Bandung Regency, with pre-test results of 57.2 and post-test results of 79.6. Conclusion: By providing knowledge about diabetes mellitus to women of childbearing age (15-49 years) in the working area of the Pakutandang Community Health Centre in Bandung Regency, the knowledge of women of childbearing age (15-49 years) in the working area of the Pakutandang Community Health Centre in Bandung Regency increased. Thus, this community service activity can have an impact on improving the health